Candida in Lower Respiratory Tract Increases the Frequency of Acute Exacerbation of Chronic Obstructive Pulmonary Disease: A Retrospective Case-Control Study - Zuo, Yi-hui; Wang, Wei-qin; Chen, Qi-jian; Liu, Bin; Zhang, Feng-ying; Jin, Xiao-yan; Hang, Jing-qing; Li, Hua-yin; Bao, Zhi-yao; Jie, Zhi-jun; Wang, Gui-fang; Gao, Xi-wen; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Objective: To explore impact of Candida on the acute exacerbation of chronic obstructive pulmonary disease (AECOPD) outcome. Methods: A retrospective, multi-center, case-control study was performed. Patients hospitalized for AECOPD in 25 centers during Jan 2011–Dec 2016 were enrolled. Data were collected, including demographic information, conditions during the stable phase of COPD, clinical characteristics of AECOPD, and follow-up information within 1 year after discharge. Univariate analysis and binary logistic regression were applied, and p < 0.05 was regarded as significant. Results: Totally 1,103 patients were analyzed, with 644 lower respiratory airway (LTR) Candida positive cases and 459 Candida negative controls. Long-term prognosis was significantly different between Candida positive and negative group, including the recurrent AECOPD within 180 days (75.5 vs. 6.6%, p < 0.001) and mortality within 1 year (6.9 vs. 0.4%, p < 0.001). Univariate logistic analysis showed that LTR Candida isolation was related to higher recurrence rate of AECOPD within 180 days and mortality within 1 year. Binary logistic regression analysis demonstrated that LTR Candida isolation was independently associated with recurrence of AECOPD within 180 days. Conclusions: LTR Candida isolation was associated with worse long-term prognosis of AECOPD and independently related to higher risks of recurrent AECOPD within 180 days.